Pemberdayaan dan Pengolahan Produk Durian di Desa Juru Mapin, Kecamatan Buer, Kabupaten Sumbawa - Yadi Hartono; Ade Mariyam Oklima; Alia Wartiningsih (Institut Pertanian Bogor, 2019)
This community partneship program (PKM) is aimed to improve knowledge and skill ofthe two community groups in Jurumapin Village, Sumbawa Regency, namely Saling Angkat farmer groupand Palopo Durian processing group that focuses on develoving the production, marketing and bussines management. This PKM program had been done from March until May 2018 through training and mentoring method. The form of science and technology implementation in the training and mentoring was the technique of cultivating and rejuvenating the durian tree, the technique of using the dog hunter to expose monkey, the technique of marketing and bussines management, and the procedures of producing some cakes from durian. The result of this PKM shows that both of the groups understand the technique of cultivating and rejuvenating the durian tree, the technique of using dog hunter to expulse monkey, the technique of using facebook as social media in online media marketing and they are able to produce some cake from durian.